A rare giant fibroepithelial stromal polyp arising from the areola of breast-a case report - Meegada, Someswara Rao; Noah, Bithika (International Surgery Journal, 2022)
Fibro-epithelial stromal polyps (FSP) are benign mesodermal tumors. They are rarely seen in the breast. Most of them arise from the nipple. Other sites of origin are the external auditory canal, the tonsil, the ureter, oropharynx, the nasal vestibule, the eyelid etc. Though the occurrence and the rarity of FSP of nipple have been described previously, a FSP arising from the areola with intact nipple hasn’t been reported in the literature till date.